In Vitro Activities of Ertapenem and Imipenem against Clinical Extended Spectrum Beta-Lactamase-Producing Enterobacteriaceae Collected in Military Teaching Hospital Mohammed V of Rabat - M. Elouennass; A. Zohoun; A. El Ameri; N. Alem; J. Kasouati; Y. Benlahlou; I. El Yaagoubi; M. Frikh; A. Lemnouer; A. Benouda (Interdisciplinary Perspectives on Infectious Diseases)
Objective. To study the sensitivity level of extended spectrum beta-lactamase-producing Enterobacteriaceae to Carbapenems (Imipenem, Ertapenem) marketed in Morocco and discusses the place of Ertapenem in the treatment of extended spectrum-beta-lactamase-producing. Materials and Methods. A retrospective study of 110 extended spectrum beta-lactamase-producing Enterobacteriaceae. Isolates obtained from blood cultures, superficial and deep pus, and catheters were conducted. The minimum inhibitory concentrations of Imipenem and Ertapenem were done by the E-test. The modified Hodge test was conducted for resistant or intermediate strains. Results. 99.1% of isolates were susceptible to Imipenem. For Ertapenem, 4 were resistant and 4 intermediate. The modified Hodge test was positive for all 08 isolates. A minimum inhibitory concentration comparison of K. pneumoniae, E. cloacae, and E. coli for Imipenem has noted a significant difference between E. cloacae on one hand and E. coli, K. pneumoniae on the other hand (𝑃<0.01). No significant difference was noted for minimum inhibitory concentration of Ertapenem. Conclusion. Our results confirm in vitro effectiveness of Ertapenem against extended spectrum beta-lactamase-producing Enterobacteriaceae as reported elsewhere. However, the emergence of resistance to Carbapenems revealed by production of carbapenemases in this study confirmed a necessary bacteriological documented infection before using Ertapenem.